THE USE OF CLOZE TESTS IN READING COMPREHENSION TEST OF THE SECOND YEAR STUDENTS OF SMAN 1 BENGKALIS (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: it was a descriptive quantitative research. This research is expected to give evidence scientifically about the result of Cloze Tests in reading comprehension test of the second year students of SMA Negeri 1 Bengkalis. The sample of this research was 126 student from the second year by using random sampling with Krejcie and Morgan table. The instrument used was Cloze Tests. The obtained data were analyzed by using SPSS version 23.0. The result of the data showed that from 126 students. It was found out that in Cloze Tests there are 81 students (64.28%) who belong to the very high category and 39 students (30.96%) belong to the high category. There are 6 students (4.76%) who belong to the average category. In other words, the researcher can conclude that the Reading Comprehension of second year students of SMA Negeri 1 Bengkalis was in very high category.Key words: Testing, Reading comprehension, Cloze Tests